Sistem Irigasi Curah Otomatis Berbasis PLC (Programmable Logic Controller) - Agus Setiawan; Gagas Dwi Lingga; Wisnu Nofiyanto; Harmen Harmen (Jurusan Teknologi Pertanian, 2013)
The objectives of this research were designed an automatic sprinkler system wake-based PLC (Programmable Logic Controller) and tested its performance. The method created/designed a sprinkler system using a pump spray gun nozzle which the pump work automatically controlled using a PLC (Programmable Logic Controller) (programmed according to the desired watering time (06:00 to 09:00 and 15:00 to 18:00)) and the system will OFF when the current effective watering daily rainfall exceeds a predetermined threshold. As for the sensor to be able to turn off the pump working as a conductor used 2 pieces detection limit of the daily effective rainfall that is placed on a measuring cup in ombrometer. Results of sprinkler irrigation system design of PLC-based automated bulk may work in settings, bulk irrigation system working width of 5.5 m, and the test results is relatively uniform water distribution. Keywords: sprinklers, automatic, PLC